СОнГУУЛИйн СУРТаЛЧИЛГаанЫ аРГа зҮй - Д.ОЮУНЧИМЭГ (Politology, 2023)
Election advertisement differs from election campaigning. In other words, an election advertisement is an information and communication process for voters from election candidates and political parties which do not include the issue of fund raising, in-party list, distribution of working groups, vote counting, dispute solving solutions and etc. Election advertisement is a very precise process performs within certain purpose, timing, strategy and tactics. It is essential not only for political parties and candidates but also for electorates to make a choice whether to be rational or irrational on election.